Single molecule biology - Knight, Alexander E. (Academic, 2008)
Single molecule techniques, including single molecule fluorescence, optical tweezers, and scanning probe microscopy, allow for the manipulation and measurement of single biological molecules within a live cell or in culture. These approaches, amongst the most exciting tools available in biology today, offer powerful new ways to elucidate biological function, both in terms of revealing mechanisms of action on a molecular level as well as tracking the behaviour of molecules in living cells. This book provides the first complete and authoritative treatment of this rapidly emerging field, explicitly from a biological perspective. The contents are organized by biological system or molecule. Each chapter discusses insights that have been revealed about their mechanism, structure or function by single molecule techniques. Among the topics covered are enzymes, motor proteins, membrane channels, DNA, ribozymes, cytoskeletal proteins, and other key molecules of current interest. An introduction by the editor provides a concise review of key principles and an historical overview. The last section discusses applications in molecular diagnostics and drug discovery. * Organized by biological system or molecule. * Each chapter discusses insights into mechanism of action, structure, and function * Covers enzymes, motor proteins, membrane channels, DNA, ribozymes, etc. * Includes an introduction to key principles and an historical overview. * Discusses applications in molecular diagnostics and drug discovery. * Provides an expert?s perspective on future developments.